2022
DOI: 10.1109/access.2021.3131329
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Geographically Weighted Regression Modeling of Urban and Rural Construction Land Fragmentation–A Case Study of the Yangtze River Delta Region

Abstract: Landscape fragmentation, which can be natural or man-made, leads to decreasing species diversity and environmental degradation. The analysis of landscape fragmentation helps people understand the relationship between land and ecosystems in order to achieve sustainable development. Using the data from 306 counties in the Yangtze River Delta region, we calculated the landscape pattern index and constructed an evaluation index for urban and rural construction land fragmentation. We used a multi-scale geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Regarding the analysis of the neighborhood built environment and walking activities among older adults, the existing cases [47][48][49] primarily focus on global relationships, whereas few studies [6,43] consider local spatial variation. Therefore, this paper reveals and expands on the spatially heterogeneous effect of the neighborhood's built environment on older adults' walking activities.…”
Section: Neighborhood Built Environment and Walking Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the analysis of the neighborhood built environment and walking activities among older adults, the existing cases [47][48][49] primarily focus on global relationships, whereas few studies [6,43] consider local spatial variation. Therefore, this paper reveals and expands on the spatially heterogeneous effect of the neighborhood's built environment on older adults' walking activities.…”
Section: Neighborhood Built Environment and Walking Activitiesmentioning
confidence: 99%
“…Furthermore, the influence intensity variety of spatial scale differences between explanatory variables on the walking of older adults is essential. For instance, Geng et al [43] reported that the scale is a crucial parameter for describing and explaining the walking difficulties of older adults.…”
Section: Spatial Scale and Main Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Since the 21st century, the state has introduced a series of strategic initiatives, from integrated urban and rural development to the construction of new rural areas. Then, the latest period of rural revitalization strategy, the "three rural" strategy, is constantly innovating [13][14][15]. The report of the 18th CPC National Congress clearly pointed out that it is necessary to vigorously promote the construction of ecological civilization and solve the problems of deterioration of human habitat, environmental pollution, and the shortage of green space in the process of urbanization [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to China's national conditions, accelerating the modernization of rural development and promoting the development of high-quality agriculture, we can effectively solve the problems of the development of various industries in society [1]. With the rapid development of digital technology and the digital economy, the construction of a digital countryside has gradually become a key step in the realization of agricultural and rural modernization and has become a necessary condition for its development, and the digitalization of rural governance is an important part of the construction of digital countryside [2].…”
Section: Introductionmentioning
confidence: 99%